TEMPOROMANDIBULAR JOINT ANKYLOSIS: EXPERIENCE WITH INTERPOSITIONAL GAP ARTHROPLASTY AT AYUB MEDICAL COLLEGE ABBOTTABAD - Abbas, Iram; Jamil, Muhammad; Jehanzeb, Muhammad; Ghous, Shah M (Journal of Ayub Medical College Abbottabad, 2005)
Background: Satisfactory surgical correction of temporomandibular joint ankylosis (TMA) is limited by a high recurrence rate, particularly in patients who underwent surgery without use of interpositional material. The present study describes our experience of Interpositional Gap Arthroplasty in patients presenting with primary or recurrent TMA. Methods: The study was conducted on 12 patients presenting at the Oral and Maxillo-Facial Surgical Unit of the Ayub Medical College Abbottabad from 1999 to 2004. Interpositioning materials used included Temporalis fascia, Temporalis muscle, Silastic sheet and Cartilage (Costochondral) graft. Pre- and Postoperative assessment of temporomandibular joint (TMJ) mobility was done by clinical assessment of jaw movement and measurement of interincisal distance by vernier calipers; X-rays were done to document complications such as fibrosis and ankylosis. Results: Nine of the 12 patients (75%) were new cases of ankylosis, while the remaining 3 (25%) had one, three and four prior operations. Duration of ankylosis ranged from 9 months to 12 years. Ankylosis was bilateral in 8 cases (66.7%) and unilateral in 4 cases (33.3%). Operative findings were simple bony ankylosis in 13/20 jaws (65%), soft tissue fibrosis in 4/20 jaws (20%) and massive bony growth in 3/20 jaws (15%). Preoperative interincisal distances ranged from 0-15mm; immediate postoperative distances ranged from 20-40 mm; one-month and six-month postoperative distances ranged from 25-50 mm. All patients had an uncomplicated outcome till six months follow up; one patient developed reduced mouth opening to 12 mm at one year follow up due to parental noncompliance with mouth exercises; one patient developed infection and extrusion of silastic sheet at 2.5 years follow up. Conclusion: Interpositional Gap Arthroplasty is a highly effective and safe surgical management option for TMA with acceptable immediate and long term outcome, particularly when temporalis fascia and muscle are used for adults and costochondral grafts with fascia interposition used for children. Key Words: Temporomandibular Joint, Ankylosis, Temporal Muscle, Arthroplasty.